VOCABULARY LEARNING STRATEGIES USED BY MALE AND FEMALE FRESHMEN OF LINGUISTICS POSTGRADUATE PROGRAM IN BRAWIJAYA UNIVERSITY - Michele Hitijahubessy (SUAR BETANG, 2018)
Vocabulary is very important in the learning process, and students have to master it. Thus awareness and understanding of vocabulary learning strategies can increase students’ vocabulary. This study aims to reveal more and less common strategies used male and female students, the difference vocabulary learning strategy between students who studied English in their undergraduate level and those who did not. In conducting this research, the researcher used survey methodology. A questionnaire adapted from the taxonomy of vocabulary learning strategies developed by Schmitt  was spread to sixteen first-year students. The most frequent strategy was “listen to English songs and news” and “using dictionary” as the most favoured strategy used by both male and female students who studied English and them who did not. From the results, it can be stated that be the students seem to enjoy learning English. Moreover, in order to increase vocabulary, both teacher and students must know about vocabulary learning strategies(Strategi Pembelajaran Kosakata yang Digunakan oleh Mahasiswa Baru S2 Linguistik Universitas Brawijaya)Kosakata sangat penting dalam proses pembelajaran dan mahasiswa harus menguasainya. Kesadaran dan pemahaman akan strategi pembelajaran kosakata dapat meningkatkan kosakata mahasiswa. Penelitian ini bertujuan untuk mengetahui strategi yang paling banyak dan paling sedikit digunakan oleh mahasiswa laki-laki dan perempuan, perbedaan penggunaan strategi belajar kosakata oleh mahasiwa baru pascasarjana ilmu linguistik yang belajar bahasa Inggris pada strata satu dan mahasiswa yang tidak belajar bahasa Inggris pada strata satu. Dalam melakukan penelitian ini, peneliti menggunakan metode survei. Kuesioner yang diadopsi dari taksonomi strategi pembelajaran kosakata yang dikembangkan oleh Schmitt diberikan kepada enam belas mahasiswa baru. Strategi yang paling sering dilakukan adalah "listen to English song and news", dan "using dictionary" sebagai strategi yang paling disukai digunakan, baik oleh mahasiswa laki-laki maupun perempuan yang belajar bahasa Inggris pada strata satu dan mahasiswa laki-laki dan perempuan yang tidak belajar bahasa inggris pada strata satu. Dari hasil tersebut, dapat dinyatakan bahwa para mahasiswa tampaknya menikmati belajar bahasa Inggris. Selain itu, untuk meningkatkan kosakata, baik guru maupun siswa harus mengetahui strategi pembelajaran kosakata.